Geophysical and geological surveys to understand the hydrogeological behavior in an outcrop area of the Guarani Aquifer System, in Brazil - de Oliveira, Mariana Vieira Galvão [UNESP]; Moreira, César Augusto [UNESP]; Netto, Leonides Guireli [UNESP]; Feitoza do Nascimento, Matheus Mistrinel Pacine [UNESP]; Sampaio, Bruna Viana [UNESP] (Elsevier, 2022)
In some Brazilian states, after the long period of drought in the years 2014 to 2015, the issue of water crises became the focus of several studies. Some of these studies propose the use of groundwater to avoid water crises. However, many of these do not understand or ignore the hydrological processes of aquifer recharge and discharge. Understanding the recharge and discharge processes is essential to prevent problems related to aquifers and better understand the exchange relationships between surface and underground reservoirs. Geophysical applications are used to study these hydrological processes of recharge and discharge, however there is a deficit regarding the use of the Electrorestivity method in this type of study. The present work delimited an area close to the escarpment of the Basaltic Cuesta front in the municipality of Ipeúna (SP). The objectives were to understand the recharge and discharge processes using the Electrical Resistivity Tomography (ERT) and a stratigraphic survey. The chosen area is in an outcrop area of the Guarani Aquifer System (GAS), a place known to be important in the recharge of this transboundary aquifer. The stratigraphic survey was carried out by walking along the access road to the study area. In the geophysical survey, 10 parallel lines of electrical resistivity tomography (ERT) were performed in Schlumberger array. The measured resistivity values ranged between 5000 Ω m and 20 Ω m. Data collected in the field were processed and represented in two-dimensional and three-dimensional logarithmic models. Through the correlation between stratigraphy and 2D models, it was possible to locate the porous and fractured aquifers, as well as to relate the resistivity values with the rocks present in the area. The 3D model provided a better visualization of the electrical resistivity values at different depths in the study area. In this way, it was possible to delimit the presence of water in the geological framework. The presence of water inside a large sandstone lens flowing towards the Cuesta front was identified. The geophysical and stratigraphy surveys provided information for the generation of a geological framework model, its relationship with groundwater flow and hydrological processes. The work also reduces the gap of geophysical studies in Guarani Aquifer System and the use of electrical resistivity tomography to understand the hydrological processes of aquifers.
Keywords: 3D model; Aquifer; Electrorestivity; Recharge and discharge